Development Of A Storage Management Model Based On Lean Warehousing: A Case Study In A Peruvian SME In The Maintenance Services Sector - Carhuas Cuyubamba, Grace (2025)
The maintenance services sector in Peru faces challenges related to inefficient inventory management and logistics operations, affecting service levels. While existing literature explores Lean Warehousing and inventory control techniques, there is limited research on tailored storage management models for small maintenance enterprises in developing economies like Peru. This research addresses this gap by developing a customized storage management model based on Lean Warehousing principles, specifically designed for small enterprises in the Peruvian maintenance sector. The case study implemented tools such as 5S and Kardex systems to optimize warehouse operations. Key results showed a 15% improvement in service level and a reduction of order processing time by 20%. The findings contribute academically by demonstrating the applicability and effectiveness of Lean tools in enhancing operational performance and competitiveness. Socioeconomically, the research supports SMEs in achieving cost reductions and improved service quality. This study calls for further exploration of integrating advanced digitalization techniques in Lean Logistics to enhance efficiency and sustainability in the sector.